"This boys club world is finally getting to me": Developing our glass consciousness to understand women's experiences in elite architecture firms. Issue 3 (19th October 2022) - Ahuja, Sumati; Weatherall, Ruth
Abstract: In this article, we take inspiration from the evolution of the material use of glass to explore how the metaphorical use of glass could be developed to understand the emerging struggles of women in architecture. Drawing on semi‐structured interviews of architects employed in professional service firms, we suggest that the multi‐faceted nature of glass helped us to identify and understand the complex experiences of inequality for women in architecture. In so doing, we make three contributions to scholarship on gender, work, and organizations. First, we demonstrate how glass barriers were truly material in their consequences for senior women, as they prevented their rise or initiated their decline. A focus on glass barriers, however, did not fully account for the experiences of younger women in these firms. Surprisingly, and in stark contrast to the "boys club world" that left many senior women in architecture with a fractured sense of self as they struggled to construct self‐affirming identities as both women and architects, we found that the exclusive use of new technologies enabled younger women architects to melt some aspects of the traditional identity and turn them into new forms. Our conceptualization of "technologies of glass" draws attention to the social, cultural, and technological resources that younger women deploy to construct a strong professional identity in the changing world of architecture. We argue that glass can be understood not just as a constraint but as a multifaceted material with limitless possibilities for design. Thus, by highlighting the material‐symbolic entanglements of the use of glass, we strengthen and refresh the metaphor of glass, to better understand the fluidity of contemporary challenges facing professional women at work.